Video Oculography Based Device Control - Bademi, Rachana R; S, Shilpa; M, Suman N; R, Praveen B (Perspectives in Communication, Embedded-systems and Signal-processing - PiCES, 2018)
Eye movements are tracked mainly using Electro-oculography (EOG), video-oculography (VOG) and electronystagmography (ENG) for detection of eye gaze. Here is a method to detect eye movements from Video-oculography. The study was started considering ALS patients. The images obtained were processed and a simple aspect is built to trace the eye movements whether it is center gaze, right gaze or left gaze.